1992
DOI: 10.1007/bf00178471
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium levels in middle ear fluids and sera in otitis media with effusion

Abstract: Middle ear fluids (MEE) and matched sera (S) were obtained from 50 patients with serous otitis media and magnesium levels were measured to determine if magnesium concentration was distinctly varied in otitis media with effusion (OME). The MEE/S ratio was considerably raised along with transient sensory hearing loss in chronic OME when compared with acute OME. The higher magnesium level found in the MEE implies that it is probably produced locally by the middle ear mucosa and may contribute to the hearing loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some antibacterial effects of Mg have also been previously reported [25,26] . Yue et al [27] reported higher Mg levels in the middle ear fluids of patients with otitis media. In the present study, we revealed that serum Mg levels were significantly reduced in COM patients compared with controls.…”
mentioning
confidence: 99%
“…Some antibacterial effects of Mg have also been previously reported [25,26] . Yue et al [27] reported higher Mg levels in the middle ear fluids of patients with otitis media. In the present study, we revealed that serum Mg levels were significantly reduced in COM patients compared with controls.…”
mentioning
confidence: 99%